2016
DOI: 10.12688/f1000research.9662.1
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of medicinal Cannabis samples; pathogenic bacteria, toxigenic fungi, and beneficial microbes grow in culture-based yeast and mold tests

Abstract: Background: The presence of bacteria and fungi in medicinal or recreational Cannabis poses a potential threat to consumers if those microbes include pathogenic or toxigenic species. This study evaluated two widely used culture-based platforms for total yeast and mold (TYM) testing marketed by 3M Corporation and Biomérieux, in comparison with a quantitative PCR (qPCR) approach marketed by Medicinal Genomics Corporation. Methods: A set of 15 medicinal Cannabis samples were analyzed using 3M and Biomérieux cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 56 publications
1
53
0
Order By: Relevance
“…While yeast models support byproduct production by synthase genes, more work is required to confirm THCA production from CBCAS or other cannabinoid synthase genes in planta . This is important to consider given the documented but rare cases of cannabis acquired aspergillosis fatalities while human exclusive THCA toxicity has never been conclusively documented (McKernan et al 2015; McKernan et al 2016; McKernan 2018b). While, the recent vaporizer fatalities are associated with THCA products, these toxicities are not attributed to the therapeutic index of THC but to the solvents (Vitamin E acetate) often used in the clandestine manufacturing practices(Blount et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While yeast models support byproduct production by synthase genes, more work is required to confirm THCA production from CBCAS or other cannabinoid synthase genes in planta . This is important to consider given the documented but rare cases of cannabis acquired aspergillosis fatalities while human exclusive THCA toxicity has never been conclusively documented (McKernan et al 2015; McKernan et al 2016; McKernan 2018b). While, the recent vaporizer fatalities are associated with THCA products, these toxicities are not attributed to the therapeutic index of THC but to the solvents (Vitamin E acetate) often used in the clandestine manufacturing practices(Blount et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite successful breeding efforts to deliver higher cannabinoid and terpene content, plant pathogens are still a significant contributor to crop loss in cannabis production due to the lack of disease-resistant varieties (Kusari 2013; Backer et al 2019). Many jurisdictions mandate cannabis microbial safety testing targeting epiphytic and endophytic plant pathogens that have been clinically linked to aspergillosis in immuno-compromised cannabis patients (McKernan et al 2015; Remington et al 2015; McKernan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Other assessments of fungal communities associated with cannabis plants have been recently conducted within the cannabis industry. These studies have amplified ITS 2 sequences from cannabis flower samples and demonstrated fungal communities placed in the order Eurotiales that included species such as Aspergillus versicolor , A. terreus , A. ostianus , A. sydowii , Penicillium citrinum , P. steckii , and P. paxilli [70, 71]. Compared to other occupational environments, workers in the cannabis production industry may be exposed to fungal plant pathogens, and disturbance activities could result in worker exposure.…”
Section: Occupational Fungal Community Analysismentioning
confidence: 99%
“…Risk of infection is an obvious concern in all patients who are immunocompromised and that concern is often heightened with the use of cannabis. Cannabis sativa , whose flowering portion contains multiple cannabinoids, has a symbiotic relationship with multiple microbes, which, like most plants, occurs mostly at the root level . However, whether the exposure to the natural flora of the cannabis plant causes an increased risk of infection to patients who are immunosuppressed is unknown.…”
Section: Concerns Voiced By the Transplant Teammentioning
confidence: 99%
“…Cannabis sativa, whose flowering portion contains multiple cannabinoids, has a symbiotic relationship with multiple microbes, which, like most plants, occurs mostly at the root level. 5 However, whether the exposure to the natural flora of the cannabis plant causes an increased risk of infection to patients who are immunosuppressed is unknown. The main concern voiced by the transplant team was risk of Aspergillus infection.…”
Section: Risk Of Aspergillus Infectionmentioning
confidence: 99%